Transcriptional control in cardiac progenitors: Tbx1 interacts with the BAF chromatin remodeling complex and regulates Wnt5a. - Li Chen (Public Library of Science (PLoS), 2012)
Mutations of the Wnt5a gene, encoding a ligand of the non-canonical Wnt pathway, and the Ror2 gene, encoding its receptor, have been found in patients with cardiac outflow tract defects. We found that Wnt5a is expressed in the second heart field (SHF), a population of cardiac progenitor cells destined to populate the cardiac outflow tract and the right ventricle. Because of cardiac phenotype similarities between Wnt5a and Tbx1 mutant mice, we tested potential interactions between the two genes. We found a strong genetic interaction in vivo and determined that the loss of both genes caused severe hypoplasia of SHF-dependent segments of the heart. We demonstrated that Wnt5a is a transcriptional target of Tbx1 and explored the mechanisms of gene regulation. Tbx1 occupies T-box binding elements within the Wnt5a gene and interacts with the Baf60a/Smarcd1 subunit of a chromatin remodeling complex. It also interacts with the Setd7 histone H3K4 monomethyltransferase. Tbx1 enhances Baf60a occupation at the Wnt5a gene and enhances its H3K4 monomethylation status. Finally, we show that Baf60a is required for Tbx1-driven regulation of target genes. These data suggest a model in which Tbx1 interacts with, and probably recruits a specific subunit of, the BAF complex as well as histone methylases to activate or enhance transcription. We speculate that this may be a general mechanism of T-box function and that Baf60a is a key component of the transcriptional control in cardiac progenitors.